Role of gonadotropin-releasing hormone 2 and its receptor in human reproductive cancers - Desaulniers, Amy T.; White, Brett R. (Frontiers in Endocrinology, 2024)
Gonadotropin-releasing hormone (GnRH1) and its receptor (GnRHR1) drive reproduction by regulating gonadotropins. Another form, GnRH2, and its receptor (GnRHR2), also exist in mammals. In humans, GnRH2 and GnRHR2 genes are present, but coding errors in the GnRHR2 gene are predicted to hinder full-length protein production. Nonetheless, mounting evidence supports the presence of a functional GnRHR2 in humans. GnRH2 and its receptor have been identified throughout the body, including peripheral reproductive tissues like the ovary, uterus, breast, and prostate. In addition, GnRH2 and its receptor have been detected in a wide number of reproductive cancer cells in humans. Notably, GnRH2 analogues have potent anti-proliferative, pro-apoptotic, and anti-metastatic effects on various reproductive cancers, including endometrial, ovarian, and prostate. Thus, GnRH2 is an emerging target to treat human reproductive cancers.